The search for Greek Catholic identity through upbringing and education - Inántsy-Pap Ágnes; Szilágyi Barnabás (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2024)
Abstract. Our aim is to present the journey travelled by the Greek Catholic Church from the establishment of the independent Diocese of Hajdúdorog until nationalization. We intend to highlight the side of the search for identity that was given as an opportunity by upbringing and education. From 1877, the Hungarian Catholic Episcopate as a central body began to manage Catholic public education. The direct local management was exercised by the maintaining local parish through the establishment of school boards from 1877. It can be dated from the same date that the Hungarian Catholic Episcopate transferred the authority of the former episcopal school-inspector to the position of the archdiocesan school-inspector who was at a higher hierarchical level. The bishop appointed the competent people to act upon the affairs of all Catholic elementary schools in the county (Mészáros 2000: 223).
Keywords: Greek Catholic Church; education